TRPV1-dependent regulation of synaptic activity in the mouse dorsal motor nucleus of the vagus nerve - Anwar, Imran J.; Derbenev, Andrei V. (Frontiers in Neuroscience, 2013)
The dorsal motor nucleus of the vagus (DMV) is a key integrative point of the parasympathetic neuronal network localized in the dorsal vagal complex. Activity of neurons in the DMV is closely regulated by synaptic inputs, and regulation of excitatory and inhibitory synapsis by transient receptor potential vanilloid type 1 (TRPV1) has been demonstrated. Activation of TRPV1 by heat, protons, endovanilloids, endocannabinoids, and inflammatory mediators is well established. In our study we hypothesized that TRPV1 contributes to the synaptic transmission of DMV neurons at physiological range of temperature without additional stimuli. Using whole-cell patch-clamp recordings we evaluated the effect of a rapid increase of temperature on excitatory and inhibitory neurotransmission and the contribution of TRPV1 to this response. Rapid increase of temperature from 25°C to 37°C increased the frequency of miniature excitatory post-synaptic currents (mEPSC) by 351.7%. The frequency of miniature inhibitory post-synaptic currents (mIPSC) also increased by 184.7%. 5'-iodoresiniferatoxin (5’-iRFT), a selective TRPV1 antagonist, prevented the increase of mEPSC and mIPSC frequency. In summary, our data demonstrate that at physiological range of temperature TRPV1 contributes to presynaptic neurotransmission of DMV neurons.